Education and mind in the knowledge age - Bereiter, Carl (L. Erlbaum Associates, 2002)
Bereiter argues that education's conceptual tools are inadequate to address the pressing educational challenges and opportunities of the times. Two things are required: first, to replace the mind-as-container metaphor with one that envisions a mind capable of sustaining knowledgeable, intelligent behavior without actually containing stored beliefs; second, to recognize a fundamental difference between knowledge building and learning--both of which are essential parts of education for the knowledge age. Connectionism in cognitive science addresses the first need; certain developments in post-positivist epistemology address the second. The author explores both the theoretical bases and the practical educational implications of this radical change in viewpoint. The book draws on current new ways of thinking about knowledge and mind, including information processing, cognitive psychology, situated cognition, constructivism, social constructivism, and connectionism, but does not adhere strictly to any "camp." Above all, the author is concerned with developing a way of thinking about the mind that can usher education into the knowledge age